"We Need to Do Better by Kids": Changing Routines in U.S. Schools in Response to COVID-19 School Closures. Issue 2 (22nd March 2021) - Grooms, Ain A.; Childs, Joshua
Abstract: In March 2020, the COVID-19 pandemic forced schools across the United States to close their buildings and educational professionals transitioned to working from home. This paper explores how K-12 principals leading schools serving high numbers of students from racially and socioeconomically minoritized backgrounds made sense of and responded to the pandemic. In particular, we examined how principals made decisions in the immediate aftermath of the school closures to best support their students and school communities during the transition to remote/virtual learning. Guided by sensemaking theory, findings indicate that principals understood the broad, societal effects of the pandemic on their students, beyond the impact of school closures. Findings also show that principals needed to navigate and make sense of policies and guidelines created by top officials and other influential external stakeholders while also engaging in sensegiving with their teachers. Finally, findings reveal that principals implemented changes and create new organizational routines in order to support their students, especially for students receiving special education services. We close with directions for future research as well as implications for understanding the impact of COVID-19 on school leadership and organizational culture.